(untitled) (Proceedings of International Educators Conference, 2024)
Digital transformation is the process of using digital technologies to improve existing business models and increase operational efficiency through it. This process will lead to full-fledged digital transformation of the entire economy, considering the application of innovative technologies on a permanent basis. Financial investments are of great importance in the efficient functioning of financial markets and in the transition to the digital economy.